A 0.5-V Biomedical System-on-a-Chip for Intrabody Communication System - Lin, Yu-Tso; Lin, Yo-Sheng; Chen, Chun-Hao; Chen, Hsiao-Chin; Yang, Yu-Che; Lu, Shey-Shi (IEEE transactions on industrial electronics (1982), 2011)
A low-voltage (0.5 V) and low-power (4.535 mW) monolithic biomedical system-on-a-chip (SOC) consisting of a receiver, a transmitter, a microcontrol unit, and an analog-to-digital converter (ADC), implemented in a 0.18-μm CMOS technology for intrabody communication is first reported. The SOC can take command through a human body and activate (or turn on) the ADC and transmitter inside the SOC. Then, a biomedical signal is converted to digital format and transmitted to the RF gateway through a human body. With this transmission methodology and the proposed SOC circuit, it is much more power efficient than wireless communication. Moreover, since no antenna is required, the chip size of the SOC is only 1.5 mm 2 , excluding the test pads.